Technology Transfer Process in Universities of India: A Long Way to Go and A Lot to Accomplish - Ahuja, Esha (2008)
The present research attempts to study the technology transferring process in universities of India. With the economic growth of more than 8%, India, like other developing countries, is focusing on improving its universities standard to match the international standard. Economic liberalization took place in 1991, and following this the Government of India is doing numerous works to keep the pace of economic development. They are funding universities and playing an important role in establishing technology parks and coming up parks include biotech- information technology (bio-it) park to encourage the growth of this emerging sector. Similar to government, industries these days are also playing a vital role for fostering technological excellence in technological university. It is has been said by scholars that industries and academia, work together for their mutual growth. In this research work, combination of both the methodology, are used to collect data. Questionnaire was send through email to faculty of various universities spread geographically across India. The statistical data analysis was conducted by applying independent-samples T-test to compare results using specialized statistical software, SPSS. This research work mainly focuses on development of technology institutes in India, shows relationship between the university and potential financer of projects, estimates the number of institute involved in the spinoff process and further determine the effect of late economic liberalization on technology transfer process and includes examples of various universities.